Artykuł oryginalnyTwo candidate gene polymorphisms in ADHD children: a case-control study of catechol-O-methyltransferase (COMT) and monoamine oxidase B (MAOB) genes - Stafi, Radim; Drtilkova, Ivana; Theiner, Pavel; Didden, William; Pitelova, Renata; Mikes, Vladimir; Sery, Omar (Archives of Medical Science, 2006)
Introduction: Attention-deficit hyperactivity disorder (ADHD) is a common polygenic heritable disorder. We have investigated the relationship between ADHD and polymorphisms of catechol-O-methyltransferase (COMT) and monoaminooxidase B (MAOB) genes. It is well known that COMT and MAOB are metabolising enzymes that degrade biogenic amines and control the levels of these neurotransmitters in the central nervous system. An association has been previously observed between the Val158Met polymorphism of catechol-O-methyltransferase (COMT) gene and ADHD. The gene of monoamine oxidase B (MAOB) has also been suggested to play a role in psychiatric disorders and behavioural traits. Moreover, MAO inhibitors have been shown to be effective in the treatment of ADHD. Material and methods: 118 boys with ADHD and 153 controls aged from 7 to 13 years were included in this study. PCR methods for the detection of the studied polymorphisms were used. Fisher’s exact test was performed to assess the association between the studied groups. Results: There was no statistically significant difference in the genotype frequency of COMT (p=0.321) or MAOB (p=0.087) gene polymorphisms between the hyperactive group of boys and the control group of boys. Conclusions: Our study supports the results of the previous studies: these two polymorphisms do not play the main role in the pathogenesis of ADHD.